Women Wheelchair Athletes: Competing against Media Stereotypes - Hargreaves, Jean Ann; Hardin, Brent (Disability Studies Quarterly, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->This study explored the attitudes and perceptions of 10 women wheelchair athletes about sports media by soliciting their opinions and concerns using both mainstream and disability print and web-based sport media. Using the "auto drive" technique for qualitative data collections, the analysis revealed three themes: (a) the participants were consumers of both mainstream and disability print media; (b) they were tired of the media stereotypes; (c) they believed that the media is partially responsible for the lack of coverage of women and individuals with disabilities in sports media as a whole. Within each of these three themes, several sub-themes emerged. Although this study was limited to female wheelchair athletes analyzing web-based and print media, the themes can provide a basis for the analysis and future study in the rising area of sports media research as it relates to females and individuals with disabilities.